Racializing Chōsenjin: Science and Biological Speculations in Colonial Korea. Issue 4 (1st December 2019) - Hyun, Jaehwan
Abstract: Recent literature on the history of medicine in colonial Korea has revealed that Japanese medical scientists studied Korean bodies to expose racial differences between the Japanese and Koreans and justify Japanese colonial rule. Previous scholars, however, have focused mainly on finding a connection between colonial medical research and eugenics. This article attempts to consider things as yet underinvestigated, in particular, the way in which medical research on Koreans emerged and was intertwined with Japanese colonialism in other ways, separate from contemporary eugenics projects. The article examines the emergence and development of what we now considered as "racial sciences"—physical anthropology, serological anthropology, and human genetics—with regard to the biological characteristics of Koreans. In doing so, it argues that biological speculations on Koreans originated as a subdiscipline of Japanese origin studies and resonated with a newly emerging type of colonial racism in colonial Korea—inclusionary racism. The article also presents the colonial scientific enterprise's conclusion that Koreans were biologically heterogeneous, contradicting colonial Korean intellectuals' assertion about Korean ethnic homogeneity. The use of Korean ethnic homogeneity as an ideological basis for nation building by two Korean governments meant that postcolonial Korean scientists had to seek a way to reconcile the colonial era's "scientific conclusion" (biological heterogeneity) with the postcolonial era's "politically approved" conceptualization (biological homogeneity). Therefore, regardless of whether it was trying to refute, appropriate, or revitalize the colonial legacy, biological research on Koreans in the postcolonial period was carried out under the framework that had been constructed by colonial racial sciences.